Гендерні та вікові відмінності мови у Інтернет-комунікації - Пелещишин, Андрій; Федушко, Соломія (Видавництво Національного університету "Львівська політехніка", 2010)
This article considers current problem of investigation and development of authentication of the given Web-forum member’s personal data. Methods of gender and age differences of Web-forum member’s messages are investigated.
Keywords: методи перевірки достовірності; гендерні відмінності; вікові відмінності; Веб-форум; користувачі; аккаунт